Just American wars ethical dilemmas in U.S. military history - Patterson, Eric 1971- (War, conflict and ethics, 2019)
This book examines the moral choices faced by US political and military leaders in deciding when and how to employ force, from the American Revolution to the present-day. Specifically, the book looks at discrete ethical dilemmas in various American conflicts from a just war perspective. For example, was the casus belli of the American Revolution just, and more specifically, was the Continental Congress a 'legitimate' political authority? Was it just for Truman to drop the atomic bomb on Japan? How much of a role did the egos of Kennedy, Johnson and Nixon play in prolonging the Vietnam War? Often there are trade-offs that civilian and military leaders must take into account, such as General Scott's 1847 decision to bombard the city of Veracruz, in order to quickly move his troops off the malarial Mexican coast. The book also considers the moral significance and policy practicalities of different motives and courses of action. The case studies provided highlight the nuances and even limits of just war principles, such as just cause, right intention, legitimate authority, last resort, likelihood of success, discrimination, proportionality, and principles for ending war such as order, justice, and conciliation. This book will be of interest for students of just war theory, ethics, philosophy, American history and military history more generally."--Provided by publisher